Peruvian Matrimonial Regime - Cornejo Chávez, Héctor (1985)
The paper analyzes the Peruvian marriage regime, addressing its evolution and the legal principles that support it. In this sense, it highlights Article 5 of the Political Constitution of Peru of 1979, which recognizes various forms of marriage, such as civil and religious, but without establishing multiple legal regimes for each. That is, it is argued that the expression “forms” refers to the formalities of the act of celebration of marriage, so it cannot be understood as synonymous with classes or types of marriage. Furthermore, the author discusses the possibility that the Peruvian State may accept different marriage systems based on religious confessions, without this implying a plurality of marriage regimes. Finally, the work highlights the importance of maintaining the juridical unity of marriage and that the legal effects be uniformly regulated by the State.